The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/0037-8682-0557-2019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the frequency of neuroimaging findings in congenital infection by Zika virus and differences between computed tomography and magnetic resonance imaging in the detection of alterations

Abstract: Introduction: Congenital infection by the Zika virus (ZIKV) is responsible for severe abnormalities in the development of the central nervous system. The aim of this study was to evaluate and compare the ability of computed tomography (CT) and magnetic resonance (MR) to detect patterns of involvement of the central nervous system in congenital ZIKV syndrome. Methods: We retrospectively analyzed CT and MR images from 34 patients with congenital ZIKV syndrome and evaluated the differences between the two methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition, a previous study conducted in a pediatric cohort (n=23) followed from birth until 36 months reported the development of postnatal microcephaly, mainly in children with severe brain abnormalities at birth 39 . Brain imaging techniques such as computed tomography (CT) and magnetic resonance imaging (MRI) showed calcifications, ventriculomegaly, and diffuse cortical atrophy, which are now part of the diagnostic criteria 31 , 35 , 40 - 42 . A multicenter study of 83 children born with microcephaly at the peak of the epidemic, recruited from 10 Brazilian states, highlighted a phenotype known as the fetal brain disruption sequence, which is rarely observed in other congenital infections 43 .…”
Section: Spectrum Of Congenital Zika Manifestationsmentioning
confidence: 99%
“…In addition, a previous study conducted in a pediatric cohort (n=23) followed from birth until 36 months reported the development of postnatal microcephaly, mainly in children with severe brain abnormalities at birth 39 . Brain imaging techniques such as computed tomography (CT) and magnetic resonance imaging (MRI) showed calcifications, ventriculomegaly, and diffuse cortical atrophy, which are now part of the diagnostic criteria 31 , 35 , 40 - 42 . A multicenter study of 83 children born with microcephaly at the peak of the epidemic, recruited from 10 Brazilian states, highlighted a phenotype known as the fetal brain disruption sequence, which is rarely observed in other congenital infections 43 .…”
Section: Spectrum Of Congenital Zika Manifestationsmentioning
confidence: 99%
“…Since the initial reports and observations of ZIKV affecting development, it has become clear that there is variation in the extent to which exposure to ZIKV during fetal development [herein, for brevity referred to as fetal ZIKV (fZIKV)] affects the developing brain and that children born with normal-sized heads and brains may also be affected. Children with congenital ZIKV syndrome (CZS), which presents both with and without microcephaly, have a myriad of neurological symptoms, including ventriculomegaly, lissencephaly, areas of calcification and cysts throughout the brain, and cortical malformations (2)(3)(4)(5)(6)(7). Children with CZS can present smaller in size and weight (8)(9)(10) and may exhibit muscle weakness, loss of reflexes, dyspnea, hypertonia, spasticity, arthrogryposis, epilepsy, and developmental delays and may have severe learning disabilities [for a review, see (11)].…”
Section: Introductionmentioning
confidence: 99%